If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 2) + -4(x + -3) = 0 Reorder the terms: 3(2 + 2x) + -4(x + -3) = 0 (2 * 3 + 2x * 3) + -4(x + -3) = 0 (6 + 6x) + -4(x + -3) = 0 Reorder the terms: 6 + 6x + -4(-3 + x) = 0 6 + 6x + (-3 * -4 + x * -4) = 0 6 + 6x + (12 + -4x) = 0 Reorder the terms: 6 + 12 + 6x + -4x = 0 Combine like terms: 6 + 12 = 18 18 + 6x + -4x = 0 Combine like terms: 6x + -4x = 2x 18 + 2x = 0 Solving 18 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 2x = 0 + -18 Combine like terms: 18 + -18 = 0 0 + 2x = 0 + -18 2x = 0 + -18 Combine like terms: 0 + -18 = -18 2x = -18 Divide each side by '2'. x = -9 Simplifying x = -9
| x+7+4x=-13 | | -10j-2j-(-20j)-(-4j)+8j=-20 | | 4Y+17=29 | | .5n+5=3+n | | -9j+15j+9j-12j-(-19)=-14 | | -3b-17-5b=2b-10-20b-7 | | 7x-2(3x-5)=2 | | 15w+w+-12=15-12+w | | 63-16x=12 | | ax+b(x+c)=dx | | 2.5(6-2p)=p+11 | | f(-1)=2x-7 | | c=4n-15 | | 7w-(-4w)-18w+2=-19 | | -8(x-2)+24=-40 | | f(-2)=2x-7 | | r+(-18r)+18r=-18 | | .5n=3n-12 | | 6x+5=-x-72 | | (y-2x+8)-(z-3y+5)+(z-4x-5m)= | | -7(-3-4x)=-315 | | -8-2x=-7x+22 | | (-3/2)/(-10/7)=x | | 19a+27b=43 | | -1/6x-8=7 | | 5*5*5*5*5*5*5*5*5*5=a | | 5*5*5*5*5*5*5*5*5*5=9765625 | | 5*5*5*5*5*5*5*5*5*5=x | | -2(4y-7)+4y=5+3(4y-3) | | 2+4x=2x+18 | | 13s^2+42s=0 | | 17x-7-13x=13x+7-13x |